Diagnóstico tardio da tuberculose em Boa Vista-Roraima: estudo de prevalência e seus determinantes - Souza, Ana Lília Guimarães Barros de (2013)
Tuberculosis (TB) is among the top ten causes of death worldwide, and Brazil integrates a group of nations representing 80% of all reported cases. One of the biggest barriers to effective TB control is represented by the delay in diagnosis, which keeps the infected individual as a potential source of transmission in the community for a longer period. The present study has as main objective to determine the incidence of delayd diagnosis of TB in Boa Vista, and the factors that influence this phenomenon. The present project was designed as a quantitative cross-sectional study, to assess the prevalence of delaid diagnosis among the cases of tuberculosis diagnosed in Boa Vista between January 2007 to December 2011, and to collect individual , socioeconomic and clinical informations, potentially related to the early and late diagnosis of TB. During the study period, 426 cases of TB were registered, and of these, 186 cases (44%) were recorded in the Hospital Geral de Roraima, a tertiary health institution in the state. Delayd diagnosis mainly affects the economically active population, represented by the male patient with a mean age of 40 years. From the social point of view, the main risk factors were lower nominal income and illiteracy. In our series of delayd diagnosis, chest X-ray showed a very effective aid in the diagnosis of TB, but with respect to smear, in 38.2% of cases it was negative, and the tuberculin skin test was also negative in most cases, demonstrating that these are exams of minor importance for the diagnosis of TB, due to large amount of false negative reactions. The main comorbidities were alcoholism, diabetes and AIDS. Delayd diagnosis is related to barriers to access to health services at primary health care level. The health professional must have a high degree of clinical suspicion for the diagnosis of TB, particularly in the face of the three major comorbidities: alcoholism, diabetes and AIDS.